Kajian Aktivitas Neurofarmakologi Acorus calamus Linn - Rafika Thahirani Safira; Anggadiredja, Kusnandar (Acta Pharmaceutica Indonesia, 2023)
ABSTRACT Jeringau (Acorus calamus Linn) is one of the plants often used in traditional Indian medicine, practiced to treat various disorders, including nervous, digestive, respiratory, metabolic, renal and hepatic. This study provides an overview of Acorus calamus Linn in terms of morphology, active constituents and neuropharmacological activity. A review of related literature from the Google Scholar, Pubmed, Reserch Gate, and Science Direct. databases showed the of neuroprotective, antiamnestic, anticholinesterase, antidepressant and anticonvulsant activities. Key words: Acorus calamus Linn, jeringau, chemical contents, neuropharmacological activites